Madura Bull Racing from an Islamic Perspective: A Study of Ethics, Animal Welfare, and Cultural Preservation - Hayyul Mubarok; Setya Yuwana Sudikan; Suhartono Suhartono (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2026)
This study examines Madura bull racing as ancestral cultural heritage with significant historical, social, and economic value. However, from an Islamic perspective, this practice has generated considerable debate within the community. Although the tradition has become an annual event supported by the government, previous practices have, in some respects, inadequately addressed animal welfare. It analyzes animal welfare ethics within the framework of Islamic jurisprudence (fiqh), specifically focusing on ḥuqūq al-ḥayawān, and assesses cultural preservation from the Islamic perspective of al-‘ādah muḥakkamah. A descriptive qualitative method was used to analyze interview data from informants, including youth leaders, religious figures, former practitioners, and current practitioners. The findings indicate that the Madura bull racing tradition previously involved the use of balm, chillies, and sharp objects to hasten the animals, constituting animal cruelty, which is prohibited by Islam. Following criticism from various societal sectors, regulations now prohibit such objects, allowing only the use of whips. Regarding animal welfare, owners provide special care by feeding the bulls herbal remedies made from free-range chicken eggs, housing them in high-quality pens, and ensuring monthly veterinary health checks. However, interviews revealed that some individuals continued to secretly employ old methods, violating the rules. As currently regulated, bull racing aligns with Islamic principles, since acts of violence are no longer permitted; what remains is not a flaw in the tradition itself but the failure of a few participants to comply, indicating a need for firmer oversight and enforcement.